A Clampdown on Service Refusals by Bangkok Taxis. Issue 1 (March 2019) - Nimmanunta, Kridsda; Amornpetchkul, Thunyarat (Bam)
One of Bangkok's most perennial problems was the misbehaviour of taxi drivers. In only 4 months, from October 2015 to January 2016, the Department of Land Transport under the Ministry of Transport (MOT) of Thailand received almost 15, 000 complaints regarding the quality of services provided by Bangkok's taxi drivers. The number one complaint was passenger refusal. Anybody taking a taxi, particularly during rush hour, was likely to get frustrated with some taxi drivers, who got flagged down but refused to go to the requested destinations. Several attempts had been made by the MOT to resolve the issue of taxi drivers refusing passengers, including imposing fines and suspending taxi drivers, allowing fare raise to improve taxi drivers' well-being, hoping to provide higher quality services and to abide by the laws and regulations. So far, the results had been unsatisfactory. This case aims to show the beauty and usefulness of real options in real-world applications by looking at one of Bangkok's most perennial problems of taxi drivers refusing passengers. A real option is a powerful framework for business, finance and economic decisions. Not only that, but it is also a versatile tool for resolving social issues.